Length of hemodialysis, fluid intake, and quality of life in patients with chronic kidney disease - Ringgani, Foulla Givfa; Krisnasary, Arie; Kamsiah, Kamsiah (Alma Ata University Press, 2024)
ABSTRAKLatar Belakang:Terapi hemodialisis jangka panjang mempengaruhi kualitas hidup pasien CKD. Mutu hidup pasien ginjal termasuk dampak dari lamanya menderita hemodialisis dan asupan cairan yang dikonsumsinya. Asupan cairan untuk pasien hemodialisis dibatasi sekitar 500 ml ditambah pengeluaran urine agar tidak terjadi penumpukan cairan. Kualitas hidup pasien CKD dapat diketahui melalui kuesioner Kidney Disease Quality Of Life (KDQOL).Tujuan: Tujuan dari penelitian tersebut termasuk supaya menemukan kaitan lama hemodialisis dan asupan cairan dengan mutu hidup pasien RSUD Bengkulu penderita gagal ginjal kronik dengan hemodialisis.Metode: Penelitian tersebut memakai desain cross sectional. Sampel pada penelitian tersebut termasuk 42 pasien yang dipilih dengan purposive sampling yang memakai kriteria inklusi serta eksklusi. Hasil analisis data menggunakan uji chi-square.Hasil: Hasil penelitian memaparkan jika ada kaitan antara lama menjalani hemodialisis dengan mutu hidup pasien RSUD Bengkulu yang menderita gagal ginjal kronik yang menjalani hemodialisis (p value = 0,046). Tidak ada hubungan asupan cairan dengan mutu hidup pasien RSUD Bengkulu yang menderita gagal ginjal kronik yang menjalani hemodialisis (p value = 0,68).Kesimpulan: Ada kaitan antara Lama menderita Hemodialisis dengan mutu Hidup Pasien RSUD Bengkulu yang menderita Gagal Ginjal Kronik dengan Hemodialisis dan tidak ada hubungan asupan cairan dengan mutu hidup pasien gagal ginjal kronis dengan hemodialisis.KATA KUNCI: KDQOL; hemodialisis; asupan cairan; kualitas hidupABSTRACTBackground: Prolonged HD therapy affects the patient's quality of life. Renal patients' quality of life is influenced by the length of their HD and the volume of fluids they ingest. To prevent fluid buildup, HD patients are only permitted to drink about 500 ml of fluid daily in addition to their urine output. Patients with CKD can evaluate their quality of life using a questionnaire known as the Kidney Disease Quality of Life (KDQOL).Objectives: This study aims to evaluate the efficacy of HD therapies, fluid intake, and clinical outcomes of patients with chronic kidney disease at General Hospital Bengkulu.Methods: This study's design was cross-sectional. The inclusion and exclusion criteria were used to select the 42 patients who would make up its purposive sampling sample. The data were assessed using the chi-square test.Results: The results show a long-standing association between HD therapy and patients with chronic kidney disease who receive HD at General Hospital Bengkulu (p-value = 0.030). In patients with chronic kidney disease receiving HD at General Hospital Bengkulu, fluid intake and quality of life are unrelated (p-value = 0.68).Conclusion: The quantity of HD and the standard of living of people with chronic renal failure are correlated. Patients with Chronic Renal Failure Undergoing HD at General Hospital Bengkulu; No Relationship Between Fluid Intake and Quality of Life of Patients with Chronic Kidney Disease Undergoing HD at General Hospital BengkuluKEYWORDS: KDQOL; hemodialysis; fluid intake; quality of lifeReceived: August 14, 2024; Revised: Nov 18 2024; Accepted: Nov 20, 2024; Available online: Nov 30, 2024; Published: NOv 30, 2024.